2020
DOI: 10.1007/s00520-019-05275-1
|View full text |Cite
|
Sign up to set email alerts
|

Let us talk about death: gender effects in cancer patients’ preferences for end-of-life discussions

Abstract: Purpose Patients with advanced cancer often receive suboptimal end-of-life (EOL) care. Particularly males with advanced cancer are more likely to receive EOL care that is more aggressive, even if death is imminent. Critical factors determining EOL care are EOL conversations or advance care planning. However, information about gender-related factors influencing EOL conversations is lacking. Therefore, the current study investigates gender differences concerning the content, the desired time point, and the mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 44 publications
3
37
0
2
Order By: Relevance
“…The aforementioned questions and participant responses about talking about death with terminally ill patients with cancer underscore the communication skills that should be taught as a part of nursing education using hands-on activities. Past studies have found that training students to focus on the emotions that are elicited by death and death-related stimuli and clinical experience alleviate the traumatic impact of death and their fear of death (Seifart et al, 2020;Strang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned questions and participant responses about talking about death with terminally ill patients with cancer underscore the communication skills that should be taught as a part of nursing education using hands-on activities. Past studies have found that training students to focus on the emotions that are elicited by death and death-related stimuli and clinical experience alleviate the traumatic impact of death and their fear of death (Seifart et al, 2020;Strang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, nurses may sometimes fail to support patients during the terminal period, and this can lead to a sense of ambiguity and the adoption of inappropriate approaches, such as ignoring their death anxiety and existential suffering (Strang et al, 2014). Consequently, terminally ill patients with cancer often receive suboptimal end-of-life care (Seifart et al, 2020). Past studies have found that terminally ill patients need existential support and the opportunity to talk about death (Breitbart et al, 2018;Gurdogan et al, 2019).…”
mentioning
confidence: 99%
“…Other regions of the country with large minority populations are witnessing the same phenomenon within Laino and Native American population ( CDC 2020b ). Preliminary evidence involving studies on gender, further, suggests males are more vulnerable to becoming critically ill/vulnerable with certain diseases/outcomes (i.e., heart disease, suicide, among others) than their female counterparts ( Seifart et al, 2020 ; Wenham et al, 2020 ), most notably, COVID-19. How prescient Blumenshine et al (2008) , among others, were over a decade ago.…”
Section: Purposementioning
confidence: 99%
“…In einer kanadischen Studie hatten von 278 Patienten 76 % bereits über Behandlungswünsche nachgedacht, 89 % davon sprachen darüber mit einer anderen Person, in 92 % der Fälle mit einem Familienmitglied [5]. In einer deutschen Untersuchung hatten 47 % der befragten Krebsbetroffenen in fortgeschrittenen Krankheitsstadien noch nicht oder fast nicht über das Lebensende gesprochen [17].…”
Section: Kommunikation üBer Das Lebensende Ist Viel Zu Seltenunclassified